On the units co z tym fantem zrobić and coś z tym fantem zrobić – lexical issues - Wojdak, Piotr (Papers in Linguistics, 2025)
The analysed units are not equally frequently represented in dictionaries and texts. 24 descriptions of the unit with co [what] and only 5 descriptions of the unit with coś [something] were collected (which gives the ratio of 4.8 : 1); in the balanced subcorpora NKJP [the National Corpus of Polish] and KWJP [the Corpus of Contemporary Polish], a total of 225 (178 and 47) uses of the unit with co and only 50 (42 and 8) uses of the unit with coś were counted (the ratio of 4.5 : 1). Based on entries and corpus data, the structural-lexical variance of the units was discussed, especially regarding the verbal component. Variants with the zrobić [to do] segment clearly dominate, which is why they were adopted as the conventional names for both units. The collected definitions (23 units with co and 4 units with coś) underwent analysis. The feature most of them share is the combination of synonymous components: interrogative phrases (or interrogative-dependent ones in the case of the unit with co), and infinitival groups in the case of the unit with coś. Definitions of this type (so-called multiple definitions) are criticized as regards their methodology. Therefore, a question arises as to how logically correct it is to define compounds with limited functional non-summativity (of phrasemes) and simple (apart from fant) lexical composition. The author leans towards paradoxical ‘reductive’ definitions: co z tym fantem zrobić ‘what to do with it’; coś z tym fantem zrobić ‘to do something about it.’ It is also possible to make an entry of the phrase z tym fantem and define it as a minimal phraseological unit. Despite the phraseological entanglement, it seems most natural to appropriately define the word fant itself: ‘something that is a problem’ (a meaning not recorded in dictionaries, except for the former SW [Warsaw Dictionary]). Another article will be devoted to the related fant phrases (Wojdak, in press).